A Cryptand Metal–Organic Framework as a Platform for the Selective Uptake and Detection of Group I Metal Cations. Issue 10 (20th January 2017) - Sapchenko, Sergey A.; Demakov, Pavel A.; Samsonenko, Denis G.; Dybtsev, Danil N.; Schröder, Martin; Fedin, Vladimir P.
Abstract: The metal–organic framework (MOF) complex (H3 O)2 [Zn4 (ur)(Hfdc)2 (fdc)4 ] (1, ur=urotropine, H2 fdc=furan‐2, 5‐dicarboxylic acid) incorporates cryptand‐like cavities, which can be used to separate and detect Rb + and Cs + optically. This is the first example of the effective employment of a MOF material for optical detection of these cations. Abstract : Detector MOF : (H3 O)2 [Zn4 (ur)(Hfdc)2 (fdc)4 ] (1, ur=urotropine, H2 fdc=furan‐2, 5‐dicarboxylic acid) incorporates cryptand‐like cavities, which can be used to separate and detect Rb + and Cs + optically. This is the first example of the effective employment of a MOF material for optical detection of these cations.